ASSESSMENT OF EFFICACY AND ADVERSE EFFECTS OF TRAZODONE IN THE TREATMENT OF MAJOR DEPRESSIVE DISORDER - Tunio, Ali Gul; Khan, Moosa; Das, Dial; Sarwar, Ghulam (Journal of Ayub Medical College Abbottabad, 2010)
Background: Major depressive disorder is a serious and disabling illness in the world and is common chronic and recurrent disorder. It is the fourth most important cause of worldwide loss in disability. Methods: This was prospective and open-label study, study conducted in JPMC, Karachi, to evaluate the efficacy and adverse effects in major depressive disorder individuals. A total of 40 patients irrespective of the gender, aged 18 years up to 65 years were enrolled from OPD of Psychiatry Department. Follow-up visits were carried out fortnightly after making evaluation of symptoms at baseline visit (day 0), follow-up continued till 90 days when the results were compiled. Results: Statistically significant (p<0.05) results were observed in all the parameters at the end of study, i.e., day 90. Conclusion: Among all the symptoms of major depressive disorder, trazodone proved to be more effective in controlling insomnia. Keywords: Trazodone, major depressive disorder, side effects, anxiolytics